High temperature reactor technology development in India. (November 2017) - Dulera, I.V.; Sinha, R.K.; Rama Rao, A.; Patel, R.J.
Abstract: High Temperature Reactor technology development programme was initiated in India with an aim to provide high temperature process heat for nuclear hydrogen production by splitting water. As high efficiency hydrogen production needs process heat at temperatures around 1123 K, a challenging technology development goal for the high temperature reactors was set to achieve coolant temperature of 1273 K. Currently development is in progress for a Compact High Temperature Reactor (CHTR), and a 600 MWth Innovative High Temperature Reactor (IHTR). Current design version of CHTR has 235 U based TRISO (TRistructural-ISOtropic) coated particle fuel, Beryllium oxide (BeO) as moderator, graphite as reflector, and lead-bismuth eutectic (LBE) as the coolant. The design incorporates many passive safety features for reactor heat removal. Current design version of IHTR is based on pebble bed fuel configuration with molten salt as coolant. For both the reactors, reactor heat is removed passively by natural circulation of the coolant. Technology development for these reactors include development of TRISO coated particle fuel, lead-bismuth eutectic and molten salt coolant technologies, BeO and graphite, oxidation resistant coatings, high creep strength alloys compatible to these coolants, high temperature instrumentation for these coolants, as well as high efficiency hydrogen production and electricity generation technologies. Highlights: High Temperature Reactor technology development programme for nuclear hydrogen production by splitting water. CHTR (Compact High Temperature Reactor) has prismatic bed and IHTR (Innovative High Temperature Reactor) has pebble bed. Reactor heat is removed passively by natural circulation of coolant - Lead-Bismuth Eutectic for CHTR and Molten salt for IHTR. CHTR uses BeO as moderator and partly BeO and graphite as reflector while IHTR uses graphite as both moderator and reflector. R&D include fuel, coolant, material, instrument, high efficiency hydrogen production and electricity generation technologies.